Effect of Educational Intervention Based on Social Support Received by the Spouse on Promoting Adherence to Treatment Regimen in Hypertensive Patients - Amin Arabshahi; Zabihollah Gharlipour; Abolfazl Mohammadbeigi; Siamak Mohebi (Hamadan University of Medical Sciences, 2020)
Aims: High blood pressure is one of the most important risk factors for cardiovascular disease. Social support and adherence to treatment regimen are effective factors in controlling and preventing high blood pressure complications. Therefore, the aim of this study was to determine the effect of educational intervention based on social support received by the spouse on promoting adherence to treatment regimen in hypertensive patients. Materials & Methods: The present experimental study was performed on 120 male patients with primary hypertension with their spouses who referred to the Qom city community health service centers in 2019. The eligible individuals were selected by convenience sampling method and randomly divided into two groups of test and control (60 people in each group). The data collection tools included a questionnaire of self-care behaviors, social support, a blood pressure checklist, and a hand pressure gauge. Data were analyzed by SPSS 20 software using statistical tests. Findings: The mean score of adherence to the treatment regimen and social support received by the spouse of subjects increased significantly after the educational intervention in the test group (p<0.001). Also, the mean score of systolic (p=0.007) and diastolic (p<0.001) blood pressure of patients after educational intervention in the two groups of test and control was significantly different. Conclusion: Education based on spouses social support improves adherence to the treatment regimen and reduces systolic and diastolic blood pressure in patients with hypertension.